Increased Regional Epicardial Fat Volume Associated with Reversible Myocardial Ischemia in Patients with Suspected Coronary Artery Disease - Khawaja, Tuba (J Nucl Cardiol, 2014)
Epicardial adipose tissue is a source of pro-inflammatory cytokines and has been linked to the development of coronary artery disease. No study has systematically assessed the relationship between local epicardial fat volume (EFV) and myocardial perfusion defects. We analyzed EFV in patients undergoing SPECT myocardial perfusion imaging combined with computed tomography (CT) for attenuation correction. Low-dose CT without contrast was performed in 396 consecutive patients undergoing SPECT imaging for evaluation of coronary artery disease. Regional thickness, cross-sectional areas, and total EFV were assessed. 295 patients had normal myocardial perfusion scans and 101 had abnormal perfusion scans. Mean EFVs in normal, ischemic, and infarcted hearts were 99.8 ± 82.3 cm(3), 156.4 ± 121.9 cm(3), and 96.3 ± 102.1 cm(3), respectively (P < 0.001). Reversible perfusion defects were associated with increased local EFV compared to normal perfusion in the distribution of the right (69.2 ± 51.5 vs 46.6 ± 32.0 cm(3); P = 0.03) and left anterior descending coronary artery (87.1 ± 76.4 vs 46.7 ± 40.6 cm(3); P = 0.005). Our results demonstrate increased regional epicardial fat in patients with active myocardial ischemia compared to patients with myocardial scar or normal perfusion on nuclear perfusion scans. Our results suggest a potential role for cardiac CT to improve risk stratification in patients with suspected coronary artery disease.